Pengaruh Strategi Pembelajaran HOTS (Higher Order Thinking Skill) terhadap Kemampuan Berpikir Kritis - Muhammad Fathonil Mubarok; Jaenullah Jaenullah; Dedi Setiawan; Kushendar Kushendar (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2022)
The role of the teacher is significant in improving students' critical thinking skills. Especially when it comes to the ability to think critically about the topics of Jurisprudence education, which are increasingly developing in this modern era, these topics are often considered trivial. One of them is by implementing the HOTS strategy. This study uses a type of quantitative research. The approach in this research is quantitative because this research is presented with numbers. The samples in this study were taken from students of classes VII and VIII, totaling 30 students. The data collection method uses a questionnaire and documentation method. Data analysis in this study uses chi quadrat. The results of this study can be concluded as follows: HOTS Learning Strategies influence students' Critical Thinking Ability in grades VII and VIII at MTs Wali Songo Sukajadi Bumiratu Nuban Central Lampung. This is based on the results of testing the hypothesis using Chi-Square showing that the result db = 4, then the rtable price is obtained at a significant level of 5% = 9.4888 and the rxy obtained is 10.34 greater than rtable, then (H0) is rejected and (Ha) is accepted. Thus, it means that the results of this consultation can accept the alternative hypothesis (Ha) proposed in this study is acceptable. HOTS learning strategies influence critical thinking skills at MTs Wali Songo Sukajadi Bumiratu Nuban Central Lampung with a percentage of 61.27%.